Ответ:
а) - 44; б) 15; в) - 3.
Пошаговое объяснение:
а)
11 + 2х = 55 + 3х
2 - 3х = 55 - 11
- х = 44
х = - 44
б)
- 15 - 3х = - 7х + 45
- 3х + 7х = 45 + 15
4х = 60
х = 60 : 4
х = 15
в)
- 3 (3b + 1) - 12 = 12
- 9b - 3 - 12 = 12
- 9b = 12 + 3 + 12
- 9b = 27
b = 27 : (-9)
b = -3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
а) - 44; б) 15; в) - 3.
Пошаговое объяснение:
а)
11 + 2х = 55 + 3х
2 - 3х = 55 - 11
- х = 44
х = - 44
б)
- 15 - 3х = - 7х + 45
- 3х + 7х = 45 + 15
4х = 60
х = 60 : 4
х = 15
в)
- 3 (3b + 1) - 12 = 12
- 9b - 3 - 12 = 12
- 9b = 12 + 3 + 12
- 9b = 27
b = 27 : (-9)
b = -3